Feminist ethics and social policy - DiQuinzio, Patrice, 1955-; Young, Iris Marion, 1949- (Indiana University Press, 1997)
Feminist Ethics and Social Policy presents complex social issues in light of a feminist ethical perspective. The spirited essays collected here critique gender blindness and biases in traditional ethical theory while developing more gender-sensitive theories and concepts. Taken together, they conceptualize issues of right action, social justice, and the human good out of the specifically gendered experience of diverse groups of women.
Keywords: Feminist ethics.; United States -- Social policy -- 1993-; Éthique féministe.; États-Unis -- Politique sociale -- 1993-; PHILOSOPHY -- Social.; PHILOSOPHY -- Ethics & Moral Philosophy.; Feminist ethics; Social policy; United States; Philosophy.; Ethics.; Philosophy & Religion.; Since 1993